Khái quát về địa mạo Trường Sơn Nam qua tuyến Kon Tum - Ba Tơ - An, Lê Đức; Thịnh, Võ; Tuấn, Ngô Anh; Thành, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2018)
Brief characteristics on geomorphology of Truong Son Nam Ridge (along the Kon Tum - Ba To line)